Early childhood development strategy for the world’s children with disabilities - Olusanya, Bolajoko O.; Wright, Scott M.; Smythe, Tracey; Khetani, Mary A.; Moreno-Angarita, Marisol; Gulati, Sheffali; Brinkman, Sally A.; Almasri, Nihad A.; Figueiredo, Marta; Giudici, Lidia B.; Olorunmoteni, Oluwatosin; Lynch, Paul; et al. (Frontiers in Public Health, 2024)
Early childhood is foundational for optimal and inclusive lifelong learning, health and well-being. Young children with disabilities face substantial risks of sub-optimal early childhood development (ECD), requiring targeted support to ensure equitable access to lifelong learning opportunities, especially in low- and middle-income countries. Although the Sustainable Development Goals, 2015–2030 (SDGs) emphasise inclusive education for children under 5 years with disabilities, there is no global strategy for achieving this goal since the launch of the SDGs. This paper explores a global ECD framework for children with disabilities based on a review of national ECD programmes from different world regions and relevant global ECD reports published since 2015. Available evidence suggests that any ECD strategy for young children with disabilities should consists of a twin-track approach, strong legislative support, guidelines for early intervention, family involvement, designated coordinating agencies, performance indicators, workforce recruitment and training, as well as explicit funding mechanisms and monitoring systems. This approach reinforces parental rights and liberty to choose appropriate support pathway for their children. We conclude that without a global disability-focussed ECD strategy that incorporates these key features under a dedicated global leadership, the SDGs vision and commitment for the world’s children with disabilities are unlikely to be realised.